Nanomaterials for water remediation - Hussain, Chaudhery M.; Mishra, Ajay Kumar; Mishra, Shivani B. (Walter de Gruyter GmbH, 2020)
The capability to generate potable water from polluted sources is growing in importance as pharmaceuticals, microplastics and waste permeate our soil. Nanotechnology allows for improvements in water remediation technologies by taking advantage of the unique properties of materials at this small scale